Analysis of natural rubber ecosystem productivity in traditional rubber growing region of India using MODIS satellite based NPP data - Meti S; Jacob J (PLACROSYM XXI. International Symposium on Plantation Crops, 10-12 December 2014, Kozhikode, India, pp. 97-98. Abstracts.)
Natural rubber plantation is the man made ecosystem which has twin advantage of supplying the raw material for natural rubber industries as well as enhancing the carbon sequestration of terrestrial biosphere through atmospheric CO2 fixation thus helping in reducing GHG level of earth atmosphere. Rubber has a carbon sequestration potential of 36-43 t C ha-1 yr-1 which is comparable with forest species. Productivity of any ecosystem is largely influenced by climate and edaphic factor and their interaction. In India, Kerala and Kanyakumari District of Tamil Nadu being the traditional belt of NR cultivation accounting 84 and 94;of area and production, respectively. Geographically traditionalbelt of NR cultivation lies between 72-76 degree longitude and 8-12 degree latitude with varied soil and climatic condition. Net primary productivity (NPP), an indicator of ecosystem productivity is being assessed by field sampling technique or by gas exchange technique. However these methods are ideal for field level assessment and are not ideal for regional level assessment/monitoring with spatial and temporal dimension. In this regard satelite based NPP data becoming the handier tool in monitoring and assessment of ecosystem performance spatially and temporally at regional and global level. Satellite based data has advantage of rapid coverage of large area, detection of inter annual variation, and non destructive method and cost effective. In this regard an attempt is being made to understand the variation in productivity of rubber ecosystem across the traditional belt of India and their relation with climatic factors. Such effort provide valuable information to policy makers and managers in selecting new areas to expand rubber cultivation to meet the growing demand of NR. For the present study MODIS annual NPP data covering the INdian subcontinent were downloaded for the period from 2000 to 2012 and were subjected to pre-processing and quality check. Then using the administrative boundary of Kerala and Kanyakumari District of TN, NPP data were clipped and used for further analysis. Temporal NPP data was overlaid with rubber distribution map under the GIS environment and extracted NPP data for rubber area covering only >75;of pixel. Then mean pure rubber NPP data (2000-2012) were correlated with different long term mean climate parameters. Traditional rubber growing area was divided into five geographical regions-south, south central, central, central north and northern region and did correlation of NPP with bioclimatic parameters region wise. Average annual NPP of rubber plantation in traditional NR growing region was estimated at 10 t C ha-1 yr-1. Rubber NPP showed inter annual variation and in general showed a declining trend during 2000-2012 periods. Within the traditional rubber growing area, NPP of rubber was high in southern region, moderate in central and least in central north. Similar trend was observed with respect to latitudinal ranges. With respect to longitude, NPP of rubber increased as we move from western to eastern side of the traditional region. Annual NR NPP showed significant negative correlation with mean diurnal temperature range (r=-0.88), Tmax of warmest month (r=-0.81), annual temperature range (r=-0.77) and annual precipitation (r=-0.66). However among the different regions of traditional rubber growing area relation of NPP with bioclimatic parameters showed variation indicating the regional variation in productivity of rubber. Highlight of the results is that in southern region, climatic parameters did not show much correlation with climatic parameters compared to other regions. This indicated the significant role of climate and topography in productivity of rubber ecosystem in traditional region except southern region.
Keywords: MODIS; NPP data; NR ecosystem; Traditional rubber growing region